2022
DOI: 10.1111/gcb.16159
|View full text |Cite
|
Sign up to set email alerts
|

Increased precipitation and nitrogen addition accelerate the temporal increase in soil respiration during 8‐year old‐field grassland succession

Abstract: Ecological succession after disturbance plays a vital role in influencing ecosystem structure and functioning. However, how global change factors regulate ecosystem carbon (C) cycling in successional plant communities remains largely elusive. As part of an 8‐year (2012–2019) manipulative experiment, this study was designed to examine the responses of soil respiration and its heterotrophic component to simulated increases in precipitation and atmospheric nitrogen (N) deposition in an old‐field grassland undergo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 118 publications
0
7
0
Order By: Relevance
“…During ecological succession, vegetation communities change over time, which could shift primary productivity, litter quantity, and quality, with subsequent effects on carbon and nitrogen cycle processes (Shao et al 2017;Smith et al 2015;Zhang et al 2022). Previous studies have reported that Alpine grassland succession in Qinghai-Tibet Plateau toward degradation, it is not only reduced plant biomass, soil organic carbon (C), and total nitrogen (N), but also changed the ratio of roots to shoots, soil water content, and these may weaken the C sink effect of vegetation and in turn aggravate the climate warming (Alhassan et al 2018;Jiang et al 2020;Liu et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…During ecological succession, vegetation communities change over time, which could shift primary productivity, litter quantity, and quality, with subsequent effects on carbon and nitrogen cycle processes (Shao et al 2017;Smith et al 2015;Zhang et al 2022). Previous studies have reported that Alpine grassland succession in Qinghai-Tibet Plateau toward degradation, it is not only reduced plant biomass, soil organic carbon (C), and total nitrogen (N), but also changed the ratio of roots to shoots, soil water content, and these may weaken the C sink effect of vegetation and in turn aggravate the climate warming (Alhassan et al 2018;Jiang et al 2020;Liu et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, although the stimulating function of short-term N addition on biocrust R s was supported by several past investigations (Gao et al, 2014), it is notable that the influence of N input on R s is a prolonged and complicated process (Zhang et al, 2022). With longer T A B L E 2 Impacts of N addition on soil respiration in different regions and ecosystems around the world.…”
Section: Uncertainties and Implications Of Biocrust R S Responses To ...mentioning
confidence: 81%
“…As slope increases, the importance of PRE and VPD for NEP variation gradually diminishes, because of the exacerbates soil erosion caused by PRE (Berger et al., 2010), and the reduced respiration due to water loss (L. Liu et al., 2016), respectively. It is noteworthy that VPD is always more important than SM in all slopes despite the growing importance of SM, possibly because increased SM also enhances soil respiration (J. Zhang et al., 2022), offsetting some of the positive effects, while VPD has essentially only negative effects on vegetation (Yuan et al., 2019).…”
Section: Discussionmentioning
confidence: 99%